Frontiers in Mental Health and the Environment - Marco Helbich (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
This book sheds light on the influence of the environment on people's mental health. To what extent are exposures to green space, air pollution, natural disasters, etc. related to depression or suicide? Such questions are relevant for both scientists and policy-makers. A rich collection of chapters subsumes current research frontiers originating from disciplines such as geography, public health, epidemiology, environmental science, etc. The topics covered in the book are of interest to researchers, practitioners, and professionals. The editor hopes that the scientific outcome of this book will stimulate debate about how the environment affects mental health outcomes.